Subsídios para a implementação da metodologia bim no projeto e fabricação de estruturas de aço - Mozzato, Ricardo Coelho (2013)
The BIM (Building Information Modeling) methodology shows a difference compared to the high competitiveness of the steel structures sector. With the introduction and evolution of BIM methodology in business, it s possible to generate and simulate the stages of construction, obtaining benefits like reduction in wasted material, labor and time. However, having BIM as a simulation of reality that happens in terms of design, cost and time, all at the same time, it requires a correct formulation and use, which substantially influences the way of working in companies. Based on this, this paper aims to analyze the application of BIM methodology in companies that industrialize steel structures, and provide subsidies for midsize companies to take advantage of it. Regarding the methodological procedures, this research follows four steps, and the data collection is made through interviews and direct observations. The research is characterized as a qualitative case study with multiple units of analysis, and classified as exploratory. Having this goal, after analyzing companies in the steel structures sector in northeastern Rio Grande do Sul, a draft model hangar for general use is developed, followed by the presentation of subsidies for the use of BIM methodology by companies of this branch. The results show that BIM is not fully implemented in companies, mainly for the lack of a full integration between the software used by them, also by external causes due to customers or suppliers resistance to share the projects in BIM. In addition, there are also internal problems, such as lack of knowledge on the subject, high costs getting the licenses of software and train staff, while considering the lack of availability of time required for the change in the work process and because they are working close to their limits of production capacity. The actions proposed in this research will assist in solving the problems in the implementation of BIM in steel structures companies, which, if implemented, will contribute to improving collaboration between all involved in the execution of projects, better interference detection and nonconformities in the project, anticipating problems, increasing productivity, reducing rework, among other benefits that the methodology brings, which are described in this paper